Control technique for power quality improvement of isolated wind power generation system - Goksu Gorel; Inas Fadhil (Institute of Advanced Engineering and Science, 2023)
Power quality (PQ) problems for renewable energy system (RES) is major challenge for using these systems. Amplitude, frequency, and waveform is important PQ parameters especially for standalone or isolated systems. In this paper we propose RES with wind turbine (WT) and permanent magnet synchronous generator (PMSG) to feed different loads (liner, non-liner) through AC-DC-AC converter. The PMSG operate with fuzzy logic inertia controller, to convert turbine torque form PU to Nm. The inverter stage in the converter operate according to proportional integral derivative (PID) controller with 3rd harmonic injection pulse width modulation (PWM) to regulate the AC voltage in load side. For the same case study and operating condition, we compared the result for system parameters when using ordinary PWM and using PID with 3rd harmonic injection. Voltages total harmonics distortion (THD) was less than 2% with liner loads, and 3.5% with non-liner load and the same was for current load, the voltage amplitude was between (1-1.03) PU under different wind speed by using the proposed controller.